Calcium chloride dihydrate affects the biological properties of white mineral trioxide aggregate on dental pulp stem cells: An in vitro study - Ahmed, Hany Mohamed Aly; Luddin, Norhayati; Kannan, Thirumulu Ponnuraj; Mokhtar@Makhtar, Khairani Idah; Ahmad, Azlina (Wolters Kluwer ‑ Medknow, 2018)
Introduction: Biological testing of biomaterials on dental pulp stem cells (DPSCs) is one recent advance in endodontic research. The aim of this study was to compare the cytotoxicity, cell attachment properties, and dentinogenic differentiation potential of extracts of white mineral trioxide aggregate (WMTA)/calcium chloride dihydrate CaCl2.2H2O combination (fast‑set WMTA [FS WMTA]) to that of WMTA on DPSCs. Materials and Methods: The cytotoxicity and cell attachment properties were evaluated on DPSCs using methyl‑thiazol‑diphenyltetrazolium assay and under scanning electron microscope, respectively. After 1, 3, and 7 days of incubation, the expression of four dentinogenic gene markers (BGLAP, DSPP, RUNX2, and SPP1) was examined using the real‑time polymerase chain reaction. Mann‑Whitney test and one‑way analysis of variance were used for statistical analysis (P = 0.05). Results: While WMTA showed favorable cytotoxicity and cell attachment properties, FS WMTA demonstrated severe/moderate cytotoxicity at three successive concentrations (P < 0.05), and the cell attachment properties were less favorable. However, DPSCs treated with FS WMTA extracts showed higher expressions of dentinogenic gene markers than WMTA (P < 0.05). BGLAP and SPP1 were down‑ and up‑regulated in both groups at all‑time intervals, respectively. DSPP was upregulated only in WMTA at day 3 compared to days 1 and 7 in FS WMTA. RUNX2 was upregulated at all‑time intervals only in FS WMTA. Conclusions: The addition of CaCl2.2H2O increases the cytotoxicity but enhances the dentinogenic differentiation potential of WMTA on DPSCs.